Inclusion of low levels of blood and feathermeal in practical diets for gilthead seabream (Sparus aurata) - Nogueira, Natacha (2021)
Rendered animal protein ingredients, such as feather meal and blood meal, are promising animal protein sources for the replacement of fish meal often proved to combine synergistically. Three practical diets containing similar amounts of PD/ED (22.0 mg/kJ) but differing in the amount of digestible protein were tested in sea bream juveniles of initial body weight 41.81±1.12 g. FBCM diet (40%PD) and FBM diet (42%PD) contained similar percentages of blood and feather meal (10% and 5%, respectively) but differed in the proportion of soybean / rapeseed meal. Although growth performance and feed utilization were very similar in all treatments, chemical composition showed that blood and feather meal supplementation increased significantly whole-body lipid content compared with fishmeal diet (P205A). Liver lipid content was significantly lower in fish fed FBCM diet. Whole-body fatty acids composition was similar between treatments, ranging between 242.57±14.17 mg g-1 in FBM diet and 274.62±23.95 mg g-1 for FBCM diet. Palmitic acid, oleic acid, linoleic acid; EPA and DHA were the most abundant fatty acids in both polar and neutral lipid fractions of the fish. Economical evaluation indicated that the incorporation of blood and feather meal as a substitute of fish meal decreased feed costs leading to a better economic conversion ratio.